Annona muricata Linn and Khaya grandifoliola C.DC. Reduce Oxidative Stress In Vitro and Ameliorate Plasmodium berghei-Induced Parasitemia and Cytokines in BALB/c Mice - Onohuean, Hope; Alagbonsi, Abdullateef I.; Usman, Ibe M.; Kasozi, Keneth Iceland; Alexiou, Athanasios; Batiha, Gaber El-Saber (Journal of Evidence-Based Integrative Medicine, 2021)
Annona muricata and Khaya grandifoliola are ethnomedicinally used for the treatment of malaria and have been experimentally shown to have an anti-plasmodial effect, but the mechanisms involved are not fully understood. This study investigated the effect of the ethanol extracts of their leaves on parasitemia, radical scavenging and cytokines in Plasmodium berghei ANKA-infected BALB/c mice. BALB/c mice were infected with P. berghei and treated with chloroquine, A. muricata or K. grandifoliola extract for 4 days. The percentage of parasitemia and the level of cytokine expression were determined after treatment. Trace element, phytochemical and nitric oxide (NO) scavenging activity, 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging properties assays were done to study the antioxidant effects of AN and KG in vitro. P. berghei consistently increased parasitemia in BALB/c mice. The tested doses (100-, 200-, and 400 mg/kg) of A. muricata and K. grandifoliola attenuated the P. berghei-induced elevation of parasitemia and cytokines (TNF-α, IL-5, and IL-6) in vivo during the experimental period, though not as much as chloroquine. Moreover, both extracts scavenged the DPPH and NO radicals, though A. muricata had more anti-oxidant effect than K. grandifoliola in-vitro. The ethanol extracts of A. muricata and K. grandifoliola reduce parasitemia in P. berghei-treated mice BALB/c by scavenging free radicals and reducing cytokines, though the extracts were not as effective as chloroquine
Keywords: Annona muricata, Khaya grandifoliola, Plasmodium berghei, BALB/c mice, cytokine inhibition, cerebral malaria